(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The purpose of this study is to fill this gap by analyzing Babur Mirza’s works in English translation and their influence on scientific and literary discourses in English literature. Specifically, this study aims to understand the ways his scientific heritage was interpreted, transmitted, and integrated into the English literary canon. The central hypothesis is that Babur Mirza’s scientific heritage, as conveyed through translations of his works, has played a significant role in the development of scientific thought in early modern English literature.